2005
DOI: 10.1038/ncb1342
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin-1 defines a clathrin-independent endocytic pathway in mammalian cells

Abstract: Previous studies provide evidence for an endocytic mechanism in mammalian cells that is distinct from both clathrin-coated pits and caveolae, and is not inhibited by overexpression of GTPase-null dynamin mutants. This mechanism, however, has been defined largely in these negative terms. We applied a ferro-fluid-based purification of endosomes to identify endosomal proteins. One of the proteins identified in this way was flotillin-1 (also called reggie-2). Here, we show that flotillin-1 resides in punctate stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
519
7
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(550 citation statements)
references
References 35 publications
22
519
7
2
Order By: Relevance
“…This idea is supported by the fact that flotillin-1 expression in insect cells can induce the formation of large caveolae-like vesicles (Volonte et al, 1999). Moreover, flotillin-1 has recently been described as a determinant of a clathrin-independent endocytic pathway in mammalian cells, which implicates this protein in vesicular trafficking (Glebov et al, 2006). Despite a striking sequence similarity between flotillin-1 and flotillin-2, specific recruitment of flotillin-1 to lipid bodies upon fatty-acid loading could also underline a specific function in lipid regulation or trafficking towards these organelles.…”
Section: Discussionsupporting
confidence: 53%
“…This idea is supported by the fact that flotillin-1 expression in insect cells can induce the formation of large caveolae-like vesicles (Volonte et al, 1999). Moreover, flotillin-1 has recently been described as a determinant of a clathrin-independent endocytic pathway in mammalian cells, which implicates this protein in vesicular trafficking (Glebov et al, 2006). Despite a striking sequence similarity between flotillin-1 and flotillin-2, specific recruitment of flotillin-1 to lipid bodies upon fatty-acid loading could also underline a specific function in lipid regulation or trafficking towards these organelles.…”
Section: Discussionsupporting
confidence: 53%
“…These data do not rule out the possibility that MNV-1 infection may occur through a caveolae-dependent pathway in other cell types that express caveolin. The recently described flotillindependent pathway is also raft-associated (Glebov et al, 2006) and may be inhibited by cholesterol depletion; however, our results showed that flotillin-1 depletion had no effect on MNV-1 infection, suggesting that this pathway is also not used for MNV-1 infection.The role of dynamin in both CME and caveolae-dependent endocytosis is well established, whereas its role in other endocytic pathways is less clear (Marsh & Helenius, 2006;Miaczynska & Stenmark, 2008). Here, we show that inhibition of dynamin using dynasore decreased MNV-1 infection of RAW264.7 cells, but only when added at the entry stage of infection, indicating that MNV-1 entry is dynamin-dependent.…”
contrasting
confidence: 56%
“…The observation of reggie-dependent cargo trafficking has been considered as reggie/flotillin-dependent and lipid raft bound endocytosis (Glebov et al, 2006). Our present assay with a ␤1-integrin antibody as well as earlier experiments with E-cadherin, transferrin receptor and the T-cell receptor did not detect a reggie-mediated endocytosis but discovered instead a reggie-assisted Rab11a-dependent recycling route (Solis et al, 2012Stuermer, 2010).…”
Section: Reggie In Vesicle Traffickingsupporting
confidence: 52%